FINANCIAL TECHNOLOGIES IN UZBEKISTAN: A CASE STUDY - Khojamurodov Diyorbek Ulug’bekovich (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article examines the evolution and current status of financial technologies (fintech) in Uzbekistan, focusing on the promising developments and technological innovations in the country’s financial sector. Through a comprehensive analysis, this study sheds light on the impact of fintech on various aspects of Uzbekistan’s financial landscape, including banking, payments, lending, and investment. The article also discusses the regulatory framework and future prospects for the growth of fintech in Uzbekistan.